Neurorehabilitation in Neuro-COVID - Ivet Borissova Koleva; Borislav Radoslavov Yoshinov; Radoslav Radoslavov Yoshinov (Neurorehabilitation in Neuro-COVID, 2023)
Corona-virus disease 2019 (COVID-19), caused by the newly emerged coronavirus [severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)], affected the public health in the world. Acute and chronic neurological issues, considered as consequences of COVID-19, are denominated Neuro-COVID. Physical rehabilitation should be offered to all patients with Neuro-COVID. Rehabilitation procedures begin during the acute stage and continue after hospital discharge – in post-acute phase and during long-term treatment. We present principles of neurorehabilitation (NR) in neuro-COVID. Special attention was paid to the process of NR of patients with some neurological complications of COVID-19, as follows: cerebral vascular accidents, spinal ischemic stroke, relapses of multiple sclerosis, Guillain-Barre syndrome, development of rare diseases (as cerebellar ataxia or amyotrophic lateral sclerosis /motor neuron disease/), etc. The importance of grasp and gait recovery for patients’ autonomy in everyday life is underlined. We emphasize on the impact of Information and Communication technologies (ICT) in the clinical practice: robotics, neurorobotics, virtual reality. We accentuate on the role of digital competences of members of the interdisciplinary and multi-professional rehabilitation team. We present typical and rare clinical cases (consequences and complications of COVID-19), treated by robotic neurorehabilitation. Our results demonstrated positive effects of ICT-application on the neuroplasticity, functional recovery and quality of life of neurological patients.